Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.7759/cureus.9199
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Hemoglobin A1c With Wagner Classification in Patients With Diabetic Foot

Abstract: Open Access Original Article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 10 publications
5
6
1
Order By: Relevance
“…It should be noted that since the original study objective was to measure IAs in patients with high and low circulating levels of HbA1c, respectively, the patients were selected to have either had HbA1c levels below 53 mmol/mol or above 69 mmol/mol at the time point of screening. Many patients had intermediary levels at the time point of blood sampling, where 23% of the patients with T1D patients and 16% of the patient with T2D patients were poor responders with HbA1c levels ≥ 80 mmol/mol, which is well within the area of 10–30% reported by others [ 56 , 57 , 58 ]. We find it unlikely that our key findings of an association between SNPs in INSR and HbA1c levels and poor glycaemic control, in particular, are affected by the inclusion criteria.…”
Section: Discussionsupporting
confidence: 58%
“…It should be noted that since the original study objective was to measure IAs in patients with high and low circulating levels of HbA1c, respectively, the patients were selected to have either had HbA1c levels below 53 mmol/mol or above 69 mmol/mol at the time point of screening. Many patients had intermediary levels at the time point of blood sampling, where 23% of the patients with T1D patients and 16% of the patient with T2D patients were poor responders with HbA1c levels ≥ 80 mmol/mol, which is well within the area of 10–30% reported by others [ 56 , 57 , 58 ]. We find it unlikely that our key findings of an association between SNPs in INSR and HbA1c levels and poor glycaemic control, in particular, are affected by the inclusion criteria.…”
Section: Discussionsupporting
confidence: 58%
“…In this study, we demonstrated the association of higher HbA1c levels with worse incident LEA risk. All of the above results reinforce the importance of regular monitoring and treatment of hyperglycemia including lifestyle modification and compliance to medication to decrease the incidence of LEA [ 23 , 31 ].…”
Section: Discussionmentioning
confidence: 59%
“…In our study, diabetic neuropathy and vasculopathy were seen more in patients with increased HbA1c, advancing age, increased random blood sugar, and increased duration of diabetes mellitus and showed increased amputation risk in such patients. Farooque et al reported that 26.13% of patients showed foot ulcerations, with nephropathy, peripheral neuropathy, ophthalmopathy, associated hypertension seen in 21.59%, 14.77%, 10.22%, and 15.9%, respectively [8].…”
Section: Discussionmentioning
confidence: 99%